2014
DOI: 10.1371/journal.pone.0084597
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-147 Induces a Mesenchymal-To-Epithelial Transition (MET) and Reverses EGFR Inhibitor Resistance

Abstract: BackgroundThe epithelial-mesenchymal transition (EMT) is a key developmental program that is often activated during cancer progression and may promote resistance to therapy. An analysis of patients (n = 71) profiled with both gene expression and a global microRNA assessment (∼415 miRs) identified miR-147 as highly anti-correlated with an EMT gene expression signature score and postulated to reverse EMT (MET).Methods and FindingsmiR-147 was transfected into colon cancer cells (HCT116, SW480) as well as lung can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 41 publications
3
50
0
1
Order By: Relevance
“…Previous studies have reported that Akt may be a potential target of miR-147 (13,15). To investigate how miR-147 affects AKT, and the role of Akt in miR-147 induced cell proliferation, invasion and migration inhibition, western blotting was performed to assess the expression and phosphorylation of the Akt protein and the downstream key effectors in the Akt/mTOR pathway.…”
Section: Mir-147 Repressed Cell Proliferation Invasion and Migrationmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have reported that Akt may be a potential target of miR-147 (13,15). To investigate how miR-147 affects AKT, and the role of Akt in miR-147 induced cell proliferation, invasion and migration inhibition, western blotting was performed to assess the expression and phosphorylation of the Akt protein and the downstream key effectors in the Akt/mTOR pathway.…”
Section: Mir-147 Repressed Cell Proliferation Invasion and Migrationmentioning
confidence: 99%
“…Other miRNAs including miR-144, miR-126, miR-199a-3p and miR-718, regulate the Akt/mTOR pathway in ovarian, oral, colorectal and human non-small-cell lung cancers and Kaposi's sarcoma (7)(8)(9)(10)(11). Few studies identified miRs regulating Akt/mTOR pathway in breast cancer (12)(13)(14)(15). MiR-122 was observed to inhibit the cell proliferation and tumorigenesis of breast cancer and to suppress the activation of the Akt/mTOR pathway by targeting IGF-1R, which is an upstream molecule of the Akt/mTOR pathway (12).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations